Studi Corporate Information Transparency On The Internet (e-CTI) Pada Bursa Efek Indonesia, Malaysia, Dan Thailand - Freddy Nathaniel Alexander; Tarsisius Renald Suganda; Sendy Cahyadi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
The purpose of this study is to analyze the influence of macro and micro factors on e-CTI in three countries namely Indonesia, Malaysia, and Thailand. The three countries have a partnership called Indonesia Malaysia Thailand - Growth Triangle (IMT-GT). The research sample consisted of 90 of the most liquid companies listed on the Indonesia Stock Exchange (LQ45), the Malaysian Stock Exchange (KLCI), and the Thailand Stock Exchange (SET50). The results showed that the size of the board of directors had an influence on e-CTI. If there are more boards of directors, it will increase its ability to encourage management to be more transparent. With the existence of regulations in the three countries that regulate the duties and responsibilities of the board of directors towards stakeholders, it will encourage management to be more transparent.